2021
DOI: 10.1039/d1cy00360g
|View full text |Cite
|
Sign up to set email alerts
|

The selective oxidation of glycerol over metal-free photocatalysts: insights into the solvent effect on catalytic efficiency and product distribution

Abstract: Selective oxidation of glycerol to high value-added derivatives is a promising biomass conversion pathway, but the related reaction mechanism, especially the solvent effect, is rarely studied. In this work, O-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Table 2 shows results for PyNO deprotection in aqueous suspensions of TiO 2 in the presence of intermediates produced by glycerol oxidation. [31][32][33][34][35] When the intermediates (Entries 2-6) were used, the Py yields were almost the same as the yield in the case of glycerol (Entry 1). The amount of CO 2 produced tended to increase in the following order: glyceraldehyde (Entry 2), 1,3-dihydroxyacetone (Entry 3) and intermediates having a carboxyl group (Entries 4-6).…”
Section: Use Of Possible Intermediates Derived From Glycerolmentioning
confidence: 80%
“…Table 2 shows results for PyNO deprotection in aqueous suspensions of TiO 2 in the presence of intermediates produced by glycerol oxidation. [31][32][33][34][35] When the intermediates (Entries 2-6) were used, the Py yields were almost the same as the yield in the case of glycerol (Entry 1). The amount of CO 2 produced tended to increase in the following order: glyceraldehyde (Entry 2), 1,3-dihydroxyacetone (Entry 3) and intermediates having a carboxyl group (Entries 4-6).…”
Section: Use Of Possible Intermediates Derived From Glycerolmentioning
confidence: 80%
“…Active radical capture experiments and EPR investigation established that singlet oxygen and superoxide radicals were the main reactive species in the reaction mechanism. Moreover, it was found that the oxidative esterification reaction can occur to generate new ester compounds in the glycerol acetonitrile solution [ 158 ].
Figure 11.
…”
Section: Prominent Catalysis Using Carbon Nitridementioning
confidence: 99%
“…
Figure 11. Possible photocatalytic reaction routes for glycerol oxidation over OCNN-2 in water and acetonitrile, reproduced with permission from [ 158 ].
…”
Section: Prominent Catalysis Using Carbon Nitridementioning
confidence: 99%
“…Several graphitic carbon nitrides were also employed as photocatalysts in the transformation of alcohols to aldehydes or ketones. Thus, a carbon-nanodot-doped material derived from 33 [193], a few-layered phosphorene nanostructure graphitic material [194], the basic unmodified graphitic carbon nitride 33 [119,195,196] and several 33 modified by thermal, chemical and mechanical processes [197], with N vacancies [198] and doped with P [199], O [200] and S atoms [201], could successfully catalyze the mentioned reaction under visible light irradiation. The photocatalysts were able to be reused after centrifugation or filtration without decreasing their catalytical activity.…”
Section: Heterogeneous Oxidative Dehydrogenation Of C-o Bondmentioning
confidence: 99%